Social isolation and cardiometabolic burden synergistically predict physical dysfunction in aging Chinese adults: Evidence of risk thresholds and the mediating role of frailty - Shuang Deng; Zhongqiang Guo; Siyuan He; Xuetao Sun (PLoS ONE, 2025)
Objective This study aimed to investigate the independent and synergistic effects of social isolation and multidimensional biomarkers (cardiovascular, metabolic, renal, muscular, and frailty) on physical dysfunction in middle-aged and older Chinese adults by utilizing an integrated sociobiological framework to address the limitations of the current research. Method A cross-sectional analysis was conducted using nationally representative data from the China Health and Retirement Longitudinal Study (CHARLS 2015; N = 3,756 participants aged ≥45 years). Physical dysfunction was defined as difficulty in ≥1 of 9 basic activities of daily living. Core exposures included social isolation (composite score), cardiovascular–kidney–metabolic (CKM) syndrome stage (0–4), vascular ageing (estimated pulse wave velocity [EPWV]), renal function (eGFR), body composition (appendicular skeletal muscle mass [ASM]), metabolic status (visceral adiposity index [VAI] and C-reactive protein triglyceride glucose index [CTI]), and frailty (frailty index). Multivariable logistic regression adjusted for demographic, lifestyle, and socioeconomic factors. Threshold effect models revealed nonlinear relationships. Causal mediation analysis (1000 bootstraps) was used to quantify pathway effects. Results Social isolation independently increased physical dysfunction risk by 38% (adjusted odds ratio [aOR]=1.380; 95% CI: 1.132–1.683; P = 0.002), with stronger effects in those aged <60 years (OR=1.731), males (OR=1.400), and rural residents (OR=1.679). Advanced CKM stage 4 was associated with a 4.8-fold increased risk (aOR=4.805, 95% CI: 2.691–8.579; P < 0.001). Key biomarker thresholds were identified: EPWV had an inflection point at 7.178 m/s, with 102.6% increased risk per unit below this threshold (OR=2.026; P = 0.021). A frailty index of <7.679 increased risk by 112.4% per unit (OR=2.124; P < 0.001). Frailty mediated 57.8% (β = 0.052, P < 0.001) of the effect of EPWV on dysfunction. ASM loss beyond 22.94 kg increased risk (OR=1.166, P = 0.008).Sensitivity analyses using E-values indicated that unmeasured confounding was unlikely to fully explain the observed associations. Conclusion Social isolation and multidimensional biomarkers (particularly CKM severity, vascular stiffness, and frailty) synergistically drive physical dysfunction in ageing Chinese adults. Frailty is a critical mediator of the impact of vascular dysfunction. The identified biomarker thresholds (e.g., EPWV = 7.178 m/s) offer intervention windows. Integrated strategies combining social connections (e.g., community support) with biomarker screening and targeted interventions (e.g., anti-frailty training for elevated EPWV) are essential to disrupt the “isolation–comorbidity–dysfunction” cycle.